2008
DOI: 10.1029/2008gl033957
|View full text |Cite
|
Sign up to set email alerts
|

Oceanic mesoscale eddies as revealed by Lagrangian coherent structures

Abstract: [1] We demonstrate the feasibility of using dynamical systems tools to unambiguously identify mesoscale oceanic eddies from surface ocean currents derived using climatological hydrography and altimetry. Specifically, our analysis is based on extracting Lagrangian coherent structures (LCSs) from finite-time Lyapunov exponent (FTLE) fields. The FTLE fields reveal with unprecedented detail an intricate tangle of LCSs, which are hidden in ocean surface topography maps but sometimes are apparent in ocean color imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
141
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(146 citation statements)
references
References 20 publications
2
141
1
2
Order By: Relevance
“…7 and 9). The same region has been analyzed by Beron-Vera et al (2008), who showed that the finite-time Lyapunov exponent, a widely used Lagrangian diagnostic (Haller 2001;Peacock and Dabiri 2010), does not reveal coherent material eddies. More recently, the same area was also studied by Lehahn et al (2011), who reported observations of a nearly isolated mesoscale chlorophyll patch, FIG.…”
Section: Resultsmentioning
confidence: 91%
“…7 and 9). The same region has been analyzed by Beron-Vera et al (2008), who showed that the finite-time Lyapunov exponent, a widely used Lagrangian diagnostic (Haller 2001;Peacock and Dabiri 2010), does not reveal coherent material eddies. More recently, the same area was also studied by Lehahn et al (2011), who reported observations of a nearly isolated mesoscale chlorophyll patch, FIG.…”
Section: Resultsmentioning
confidence: 91%
“…(b) EMC-CE interactions, distinguished by the moments when the surface volume transport is more than one standard deviation away from the mean represented in Fig. 15. material (Haller 2002(Haller , 2005Beron-Vera et al 2008;Samelson 2013). Here, we follow other works (e.g., Faghmous et al 2015) and treat these nearly circular SLAs as eddies, independent of their trapping ability.…”
Section: Discussionmentioning
confidence: 99%
“…Maps of FSLE are calculated weekly. An alternative to FSLE is the finite-time Lyapunov exponents (22,46). At the scales and parameters we are working no significant differences are expected for the locations of LCS by any of the 2 methods.…”
Section: Methodsmentioning
confidence: 99%